2021
DOI: 10.31234/osf.io/n4ujh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Region-specific elevations of glutamate + glutamine correlate with the sensory symptoms of autism spectrum disorders

Abstract: Individuals on the autism spectrum are often reported as being hyper- and/or hypo-reactive to sensory input. These sensory disturbances were one of the key observations that led to the development of the altered excitation-inhibition (E-I) model of autism, which posits that an increase ratio of excitatory to inhibitory signaling may explain certain phenotypical expressions of autism spectrum disorders (ASD). While there has been strong support for the altered E-I model of autism, much of the evidence has come … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…As the TE of our MRS data varied, we simulated six different PRESS basis sets for each TE (36,37,38,39,40,41) segmentation. The structural T1-image was segmented into gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the TE of our MRS data varied, we simulated six different PRESS basis sets for each TE (36,37,38,39,40,41) segmentation. The structural T1-image was segmented into gray matter (GM), white matter (WM), and cerebrospinal fluid (CSF).…”
Section: Methodsmentioning
confidence: 99%
“…Horder and colleagues (35) for example found reduced levels of glutamate in the striatum to be associated with the severity of social symptoms in ASD. Interestingly, Page and colleagues (36) found increased concentrations of glutamate/glutamine in the amygdala/hippocampus, but not in parietal regions, while others found increased glutamate in the inferior frontal gyrus (37), the sensory motor cortex (children (38)) or the putamen (39). Another study (40) found reduced glutamate concentrations in the auditory cortex and increased concentrations in the ACC.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory circuits in which GABA has a key role mature in early postnatal periods and subsequent brain development 'cascades' through multiple sensitive periods as more and more complex cognitive and behavioral skills are acquired (73). Indeed, atypical sensory processing has been flagged very early in development of infants who go on to receive a diagnosis of ASD (2,74). Thus, the atypical GABAergic auditory processing in ASD observed here is likely to reflect earlier alterations in neural circuit maturation.…”
Section: Origins Of Gaba Differences In Asdmentioning
confidence: 77%
“…In particular, alpha desynchronization may be linked to increased neural excitability/decreased neural inhibition (6). Previous studies in ASD reported abnormal cortical inhibitory interneurons (79,80) and altered glutamatergic levels (81,82), associated with atypical sensory processing in ASD (73,83). The excitation/inhibition imbalance increases neural noise in ASD and may lead to atypical sensory processing and under-responsiveness to behaviorally relevant stimuli in participants with ASD (72).…”
Section: Alpha Band: a Relevant Marker For Studying Asd Atypicalitymentioning
confidence: 99%